ANALYSIS OF HEAVY METALS IN STATE PARK “FLOR DEL BOSQUE” - José Carlos Mendoza-Hernández; Janette Arriola-Morales; Gabriela Pérez-Osorio; Ángel Silveti-Loeza; Miriam Vega-Hernández; Ana Lilia Portillo-Zapotitla; Olimpia Jaramillo- Hernández; Ricardo Morales-Juárez (Ra Ximhai, 2016)
Given the importance of conserving protected areas, and considering that human activities can affect plants and the soil and the "Flower Forest" State Park set a target of work analyzing the concentration six toxic heavy metals (Cr, Cd, Cu, Hg, Ni, Pb) in sheets of eight plant species (Quercus Mexico, Quercus rugosa, deppeana Juniperus, Juniperus flaccid, Eucalyptus camaldulensis, Eucalyptus globulus, Mimosa malacophylla and Euforbiáceas) and soil samples grouped into four different areas (pine, oak, eucalyptus and pastures) within the study area, for which vegetable samples were collected for a year and land in rainy and dry season. The samples were treated under the provisions of Mexican law to quantify metals. It notes that the six metals tested (Cr, Cd, Cu, Hg, Ni and Pb), were found in all plant species and the total fraction of the soil while the soil available in the Cr fraction was not detectable in any area, indicating that there be readily available to plants through the roots. A high correlation between Cr-Cu was found in most vegetable indicating a common source. The concentrations of metals are within permissible limits not to cause chemical injury, but they can continue to accumulate in root, stem, leaves and cause plant damage and deterioration of the protected area "Flor del Bosque Puebla."